Międzynarodowa wymiana handlowa a deformacja światowego cyklu koniunkturalnego - Jachna, Mieczysław (Wydział Prawa i Administracji UAM, 1966)
The characteristic feature of the capitalist economy are its trade cycles, alternating periods of rising and falling levels of economic activity with similar characteristics in fluctuating output prices, etc. from one cycle to another. The history of crises — one of the cycle's phases — can be traced back to the end of the XVIII century — but the first cyclical crisis of general overproduction took place only in 1825. Then the scope of economic downturn or contraction got gradually ever larger. The greatest world crisis had taken place in the years of 1929—1933. Since then the capitalist economy did not experience any world-wide depression, the world's conjuncture cycle got deformed. A certain influence on the deformation of a cycle exerts the international trade, an outer factor determining to some extent is course. The looming crisis in 1937—1938 was finally checked by the outbreak of the world war II. After the war the law of postponed demand — made itself felt in international trade relations. This situation was particularly advantageous to the highly developed capitalist countries. The first after-war collapse of conjuncture in USA took place in 1948—1949. It was not strong enough, however, to pass its impulses to the European continent, thus there was no mutual resemblance in the prevailing phases of a cycle in the two greatest industrial regions of the world, This situation repeated itself during the subsequent economic recessions which swept the two continents. The changes in export and import indices in conjuncture with specific growth or decelerating factors — explain the above mentioned dissimilarity in the phases of a cycle. The interventionist policies of a state which aim at preventing all too abrupt changes in the volumes of foreign trade and in price fluctuations, in concert with close cooperation with the monopolies and the shortdated American cycle and the feebleness of the westeuropean recessions as well as the structural changes in the international trade of the highly industrialized countries — all this contributed to the deformation of the world's cycle. On the other hand, it is difficult to measure the influence of the westeuropean integration processes in the sphere of internal trade (in the framework of a community) on mutual penetration of crisis impulses. The foreign trade can be — in that respect — even a factor which facilitates the passing on of said impulses.